Safety and Efficacy of Fecal Microbiota Transplantation for Grade IV Steroid Refractory GI-GvHD Patients: Interim Results From FMT2017002 Trial - Zhao, Ye; Li, Xuewei; Zhou, Yujing; Gao, Jin; Jiao, Yang; Zhu, Baoli; Wu, Depei; Qi, Xiaofei (Frontiers in Immunology, 2021)
Gastrointestinal (GI) tract graft-vs-host disease (GvHD) is a major cause of post-allo-HSCT morbidity and mortality. Patients with steroid-refractory GI-GvHD face a poor prognosis and limited therapeutic options. Here, we reported an interim results from FMT2017002 on the safety and efficacy of fecal microbiota transplantation (FMT) in treating steroid-refractory GI-GvHD. FMT2017002 (#NCT03148743 trial) was a non-randomized, open-label, phase I/II clinical study of fecal microbiota transplantation (FMT) in treating patients with grade IV steroid-refractory GI-GvHD. A total of 55 patients with steroid-refractory GI-GvHD were enrolled. Of them, 23 patients with grade IV steroid-refractory GI-GvHD were assigned to FMT and 18 to the control group. At day 14 and 21 after FMT, the clinical remission was significantly greater in FMT group than in control group. Within a follow up of 90 days, the FMT group showed better OS. At the end of the research, the median survival time was >539 days in FMT group and 107 days in control group (HR 3.51, 95%CI, 1.21-10.17; p=0.021). Both the EFS (HR 2.3, 95%CI, 0.99-5.4; p=0.08) and OS (HR 4.4, 95%CI, 1.5-13.04; p=0.008) kept increasing during the follow-up in FMT group. Overall, the mortality rate was lower in FMT group (HR 3.97, 95%CI, 1.34-11.75; p=0.013). No difference was observed in the occurrence of other side effects. Our data suggest that the diversity of intestinal microbiota could be affected by allo-HSCT. FMT was effective and safe in treating grade IV steroid refractory GI–GvHD.